2011
DOI: 10.1016/j.placenta.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal maternal hypoxic stress: Adaptations of the placental renin-angiotensin system in the mouse

Abstract: The normal murine placenta possesses several components of RAS, and in response to AMH several of these elements undergo important changes. In addition, differential expression of RAS mRNA, miRNA and protein, indicate post-transcriptional regulatory mechanisms involved with hypoxic stress, and necessitate further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 50 publications
3
39
1
Order By: Relevance
“…Regarding fetal lung, this study corroborated previous evidences concerning ACE, AT 1 and AT 2 expression (13)(14)(15)28). For the first time, the present study showed that renin and angiotensinogen are also expressed during lung development.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding fetal lung, this study corroborated previous evidences concerning ACE, AT 1 and AT 2 expression (13)(14)(15)28). For the first time, the present study showed that renin and angiotensinogen are also expressed during lung development.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding lung morphogenesis, there is some evidence that lung expresses ACE as well as AT 1 and AT 2 receptors during fetal development (13)(14)(15). However, RAS components expression pattern, as well as effects during lung morphogenesis, is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One specific mechanism may involve microRNAs (miRNAs), which function to downregulate protein expression without degrading the mRNA. In this regard, reduced expression of the miRNAs that putatively increase translation of ACE2 is observed in fetal lung (32). Thus, posttranscriptional epigenetic programming to increase protein translation may account for discrepancies in the pulmonary mRNA and protein levels observed in the present study.…”
Section: Ontogeny Of Ace2mentioning
confidence: 54%
“…Another possibility is that changes in expression of the angiotensin (AT) type 2 (AT 2 ) receptor can accentuate the potency of bradykinin (7,92). Indeed, in the mouse lung, AT 2 receptor mRNA expression increases following antenatal hypoxia, while AT 1 receptor expression remains stable (34). This finding mirrors the protein expression changes with ontogeny, where AT 2 receptor expression increases from the neonatal mouse to the adult, while AT 1 receptor expression is steady (25).…”
Section: Discussionmentioning
confidence: 98%